Proceedings of the 15th International Symposium on Management (INSYMA 2018) 2018
DOI: 10.2991/insyma-18.2018.58
|View full text |Cite
|
Sign up to set email alerts
|

Resource orchestration to improve communication with customers: qcase study: MSME footwear in East Javaq

Abstract: This study aims to discuss the orchestration of resources in MSME in accordance with the implementation of ISO 9001 standards and the improvement of product competitiveness. By using case study research approach at MSME footwear in East Java, the results obtained are the information on how the company is orchestrating its resources from the early stages toward the growth stage by means of the certification program of ISO 9001. In the early stages, the company owner has lots of activity of routine work and is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A recent case study by Trisnawati and Rosiawan (2018) identified how ISO 9001 implementation facilitates intra-firm resource orchestration, revealing that the standard improves the management of processes, which become more coordinated and controlled.…”
Section: Relationship Between An Ascs Scf and The Iso 9001 Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case study by Trisnawati and Rosiawan (2018) identified how ISO 9001 implementation facilitates intra-firm resource orchestration, revealing that the standard improves the management of processes, which become more coordinated and controlled.…”
Section: Relationship Between An Ascs Scf and The Iso 9001 Standardmentioning
confidence: 99%
“…Relationship between an ASCS, SCF and the ISO 9001 standard: the role of ISO 9001 as a facilitator of resource orchestration A recent case study by Trisnawati and Rosiawan (2018) identified how ISO 9001 implementation facilitates intra-firm resource orchestration, revealing that the standard improves the management of processes, which become more coordinated and controlled.…”
Section: 5mentioning
confidence: 99%